SENGKETA HAK MEREK DAGANG GEPREK BENSU MELAWAN I AM GEPREK BENSU - Catherine Angelica; Gunardi Lie; Moody Rizqy Syailendra (PROSIDING SERINA, 2021)
This study examines the dispute over the trademark rights of "Geprek Bensu" owned by Ruben Onsu with "I Am Geprek Bensu" owned by PT. Benny Sujono's Geprek Chicken. Knowing Indonesia's legal protection for trademarks and dispute resolution on trademark rights "Geprek Bensu" with "I Am Geprek Bensu" in the Commercial Court. The party entitled to a trademark is the party who first registered the mark. The research method used in this case approach is the normative juridical method. The source of data from normative juridical research is researching library materials or secondary materials. The research results show that Indonesian legal protection for trademarks applies a first to file system. One of the trademark rights disputes that has occurred in Indonesia is the seizure of the brand name "Bensu" by Geprek Bensu and I Am Geprek Bensu. Based on the decision of the Commercial Court, the application for the Geprek Bensu trademark belonging to Ruben Onsu which was registered on 7 June 2018 was canceled in its entirety. This happened because the name “Bensu” was first registered on May 3, 2017 by I Am Geprek Bensu owned by PT Ayam Geprek Benny Sujono. I Am Geprek Bensu who has registered his trademark first and obtained legal protection for his trademark rights. Ruben Onsu has also been a promotional ambassador for I Am Geprek Bensu before opening Geprek Bensu. The court's decision considered that Ruben Onsu as the trademark copyright registrar had bad faith because Geprek Bensu had similarities ranging from the product sold, the color of the logo, and the image of the chicken in the logo with the brand I am Geprek Bensu.Penelitian ini mengkaji mengenai sengketa hak merek dagang  “Geprek Bensu” miliki Ruben Onsu dengan “I Am Geprek Bensu” miliki PT. Ayam Geprek Benny Sujono. Mengetahui perlindungan hukum  Indonesia terhadap merek dan penyelesaian sengketa terhadap hak merek dagang “Geprek Bensu” dengan “I  Am Geprek Bensu” di Pengadilan Niaga. Pihak yang berhak atas suatu merek adalah pihak yang terlebih dahulu mendaftarkan mereknya. Salah satu sengketa hak merek dagang yang pernah terjadi di Indonesia adalah perebutan nama merek “Bensu” oleh Geprek Bensu dan I Am Geprek Bensu. Metode penilitian yang digunakan dalam pendekatan kasus ini adalah metode yuridis normatif. Sumber data dari penelitian yuridis normatif adalah meneliti bahan pustaka atau bahan sekunder. Didapatkan hasil penelitian menunjukkan bahwa perlindungan hukum Indonesia terhadap merek menerapkan sistem first to file. Berdasarkan putusan Pengadilan Niaga, permohonan merek Geprek Bensu milik Ruben Onsu yang didaftarkan pada 7 Juni 2018 dibatalkan secara keseluruhan. Hal ini terjadi karena nama “Bensu” pertama kali telah di daftarkan pada 3 Mei 2017 oleh I Am Geprek Bensu miliki PT Ayam Geprek Benny Sujono. I Am Geprek Bensu yang telah mendaftarkan mereknya terlebih dahulu dan memperoleh perlindungan hukum atas hak mereknya. Ruben Onsu juga pernah menjadi duta promosi I Am Geprek Bensu sebelum membuka Geprek Bensu. Putusan pengadilan menganggap bahwa Ruben Onsu sebagai pendaftar hak cipta merek dagangnya memiliki itikad yang kurang baik karena Geprek Bensu memiliki kesamaan mulai dari produk sajian yang dijual, warna logo, dan gambar ayam di logo dengan merek I am Geprek Bensu.